Legal transplantation: the making of Chinese marine insurance law - Wang, Jia (2023)
Legal transplantation is a form of law-making. Scholars have advanced many theories in an endeavour to explain precisely how legal transplantation works, or indeed to challenge whether it is a reality. However, these theories are not tested by empirical evidence. This thesis is a study of the strengths and weaknesses of the current theories of legal transplantation by subjecting them to empirical scrutiny in the context of a particular transplantation, namely the making of Chinese marine insurance law. English marine insurance law constitutes the dominant paradigm in two Chinese attempts of making marine insurance law by legal transplantation. The thesis has employed two methods to conduct this socio-legal study of the process of making Chinese marine insurance law by transplantation, namely legal historical analysis and empirical qualitative interviews. The case study will reveal that legal transplantation is extremely fact-sensitive. When tested in the Chinese experience, all the existing theories of legal transplantation are deficient in greater or lesser respect, although they make useful contributions to understanding this form of law- making.